Invasive Weeds in Parmenides’s Garden. - Ramírez Calle, Olga (Institute of Philosophy (Zagreb), 2020)
The paper attempts to conciliate the important distinction between what-is, or exists, and what-is-not, thereby supporting Russell’s existential analysis, with some Meinongian insights. For this purpose, it surveys the varied inhabitants of the realm of ‘non-being’ and tries to clarify their diverse statuses. The position that results makes it possible to rescue them back in surprising but non-threatening form, leaving our ontology safe from contradiction.
https://v2.sherpa.ac.uk/id/publication/20347
Keywords: Ontología; Meinong